IDENTIFICATION OF WATER TURBIDITY WITH TURBIDITY SENSOR BASED ON ARDUINO - Hafdiarsya Saiyar; Mohammad Noviansyah (Jurnal Riset Informatika, 2021)
Water is an important need for all living things, especially humans. Humans need water with quality that meets the physical, microbiological, chemical, and radiological requirements contained in the mandatory and additional parameters. The selection of these parameters is very important to meet the requirements of good water, namely tasteless, odorless, and colorless. Meanwhile, there are three parameters used for water identification, namely pH parameters, turbidity levels, and temperature parameters. From these problems, the authors examine the detection of water quality, especially water turbidity. The author tries to make a tool that can detect the level of turbidity of water with a turbidity sensor as a detector of the level of turbidity in the water, Arduino Uno as a processor for the data results that have been detected, and a 16x2 LCD as a display of turbidity level measurement results in the form of turbidity values ​​and descriptions of the water being tested. The measurement range that can be detected by this tool is from 0 – 3000 NTU. The research method used is direct observation of the selected object, namely the author's home environment, and conducting library research related to the Arduino microcontroller. The purpose of this study was to determine and detect the level of water quality in the community. As one of the tools or alternatives for the community to find out or detect the level of water quality early.